2016
DOI: 10.1002/2016jg003586
|View full text |Cite
|
Sign up to set email alerts
|

On the methane paradox: Transport from shallow water zones rather than in situ methanogenesis is the major source of CH4 in the open surface water of lakes

Abstract: Estimates of global methane (CH4) emissions from lakes and the contributions of different pathways are currently under debate. In situ methanogenesis linked to algae growth was recently suggested to be the major source of CH4 fluxes from aquatic systems. However, based on our very large data set on CH4 distributions within lakes, we demonstrate here that methane‐enriched water from shallow water zones is the most likely source of the basin‐wide mean CH4 concentrations in the surface water of lakes. Consistentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 38 publications
1
52
0
Order By: Relevance
“…convection (Farmer, 1975;Jonas et al, 2003;Mironov et al, 2002) and downslope gravity currents, the latter originating from differential heating in the shallows (Kenney, 1996;Kirillin et al, 2015). In lakes, these currents transport heat and biogeochemical tracers between nearshore and the interior basin (Brothers et al, 2017;Encinas Fernández et al, 2016;Farrow, 2004), supporting the biogeochemical connectivity between littoral and pelagic zones. Under-ice gravity currents have been observed, and their transport has been implicated in the basin-scale thermal structure and circulation of polar lakes (Cortés & MacIntyre, 2019;Kirillin et al, 2015).…”
Section: Introductionmentioning
confidence: 86%
“…convection (Farmer, 1975;Jonas et al, 2003;Mironov et al, 2002) and downslope gravity currents, the latter originating from differential heating in the shallows (Kenney, 1996;Kirillin et al, 2015). In lakes, these currents transport heat and biogeochemical tracers between nearshore and the interior basin (Brothers et al, 2017;Encinas Fernández et al, 2016;Farrow, 2004), supporting the biogeochemical connectivity between littoral and pelagic zones. Under-ice gravity currents have been observed, and their transport has been implicated in the basin-scale thermal structure and circulation of polar lakes (Cortés & MacIntyre, 2019;Kirillin et al, 2015).…”
Section: Introductionmentioning
confidence: 86%
“…There have been other recent indications of nonmicrobial CH 4 production, although only at very small levels insignificant in the context of the global CH 4 budget (Table ) (Wang, Lerdau, & He, ). The presence of CH 4 in oxic zones in lakes is likely driven by the transport of dissolved CH 4 from CH 4 production areas, rather than aerobic, algae‐related CH 4 production (Encinas Fernández et al, ). However, in marine environments, CH 4 production in fully oxygenated sulfate‐rich zones (see section 2.2.2) has been directly attributed to bacterial degradation of dissolved organic matter in seawater (Repeta et al, ).…”
Section: Methane In the Global Carbon Cyclementioning
confidence: 99%
“…This phenomenon is also true for methane produced in sediment of the shallow part of a deep lake. For example, findings in German lakes showed that the ratio of the surface area of the shallow water zone to the entire lake area was a better predictor of surface methane concentration than the total surface area (Encinas Ferna´ndez et al 2016). Nevertheless, studies of the distinct methane dynamics in shallow vs. deep parts of lakes at lower latitudes are needed to confirm the robustness of their conclusion.…”
Section: Perspectivesmentioning
confidence: 99%
“…Although interactions between cyanobacteria and bacteria/archaea can result in methane production in oxic layers (Bogard et al 2014), the mechanism for this process is not fully understood (summarized in Tang et al 2016). Another controversy is whether methane produced in the oxic subsurface layers makes a large (Bogard et al 2014)o r small (Encinas Ferna´ndez et al 2016) contribution to the amount of methane emitted from the lake surface. Finally, the possible production of CH 4 under aerobic conditions (Karl et al 2008;Damm et al 2008)i n marine systems has been debated.…”
Section: Perspectivesmentioning
confidence: 99%